2018
DOI: 10.1016/j.brainres.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Shared and divergent neural reactivity to non-drug operant response outcomes in current smokers and ex-smokers

Abstract: Addiction to cigarettes presents with considerable health risks and induces high costs on healthcare resources. While the majority of cigarette smokers endorse the desire to quit, only a small percentage of quit attempts lead to full abstinence. Failure to achieve abstinence may arise from maladaptive reactivity in fronto-striatal regions that track positive and negative valence outcomes, thus biasing the choice to smoke in the presence of alternative, non-drug reinforcement. Alternatively, long-term nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For cannabis-dependent inpatients, gain expectancy correlated negatively with the activation of the right anterior cingulate cortex during the anticipation of gain vs. loss. The anterior cingulate cortex is involved in error monitoring and is affected by nicotine and cannabis (59,60). For error monitoring, the expectation about an action is compared with the outcome and a deviation elicits the correction of behavioral responses (61).…”
Section: Discussionmentioning
confidence: 99%
“…For cannabis-dependent inpatients, gain expectancy correlated negatively with the activation of the right anterior cingulate cortex during the anticipation of gain vs. loss. The anterior cingulate cortex is involved in error monitoring and is affected by nicotine and cannabis (59,60). For error monitoring, the expectation about an action is compared with the outcome and a deviation elicits the correction of behavioral responses (61).…”
Section: Discussionmentioning
confidence: 99%
“…Many comparative studies of past smokers suggest factors that may facilitate prolonged abstinence. For example, when studying reward outcomes on the monetary incentive delay task, one fMRI study identified reduced BOLD signal in both current and past smokers in the left amygdala during monetary gain and in the ACC during monetary gain/loss, and past smokers showed increased BOLD signal in the right amygdala during monetary loss; the latter suggesting alterations in negative valence processing in past smokers that may facilitate abstinence [68]. Another study compared past smokers to current smokers and nonsmokers in two fMRI experiments on an attention bias task, measuring cue-reactivity, and a go/no-go task, measuring error monitoring and response inhibition [69].…”
Section: Introductionmentioning
confidence: 99%